Improved Optimization of the Nominal Functioning of a New Global High Voltage Power Supply N=2 Magnetrons for Microwaves Generator - Belhaiba Abderrahim; N. Elghazal; M. Chraygane; M. Ferfra; B. Bahani; M.Ould Ahmedou (Institute of Advanced Engineering and Science, 2012)
This work deals with the energetic validation of a new optimized high voltage power supply for micro-waves generators with N=2 magnetrons that are used as an energy source in industrial applications. In this article, we will apply an optimization strategy that aims at improving the nominal functioning of the optimized power supply with N=2 magnetrons. Unlike research work already done an this topic, this article treats the correct energetic functioning of the two magnetrons. An equivalent scheme in π of the transformer model is presented with the geometrical parameters taken as reference. This model has been tested with the help of the simulation software Matlab-Simulink close to nominal operation. The theorical results compared to the experimental measures are in good conformity. Following that, we will validate the functioning of the new optimized power supply by calculating the average power and then comparing it with that which was found for the power supply with geometricals parameters taken as reference.DOI:http://dx.doi.org/10.11591/ijece.v2i5.1588